A new approach to investigate effects of biodegradation on pyrrolic compounds by using a modified Manco scale. (1st April 2020) - Sun, Peng; Cai, Chunfang; Tang, Youjun; Tao, Zhiqiang; Zhao, Wei
Graphical abstract: With increasing Manco Number 2 values, 1-/(2-+3-) and 1, 8/2, 7-dimethylcarbazole, and semi-shielded/exposed carbazole show two-stage variation patterns, indicating that they cannot be used to reflect migration distances. Highlights: Manco Number 2 shows higher resolution than the PM level of oil biodegradation. Benzocarbazoles are the last to be biodegraded among pyrrolic compounds. 1-/(2-+3-) and 1, 8/2, 7-dimethylcarbazole show two-stage variation patterns. Semi-shielded/exposed carbazole ratios cannot reflect migration distances. Abstract: Biodegradation of pyrrolic compounds which are not in the Peters and Moldowan's scale (PM level) has been rarely reported. A suite of oil samples produced from the Neogene Guantao (Ng) Formation in the Bohai Bay Basin were analyzed. They have similar maturity and were derived from similar parent organic matter. The oil samples were assorted into different biodegradation degrees by using modified Manco Number 2 (MN2). Carbazole, methylcarbazole and dimethylcarbazole are found to have been biodegraded, resulting in the decrease in their absolute concentrations with increasing MN2. Alkylcarbazoles are found to be more susceptible to biodegradation than benzocarbazoles, among which, benzo[b]carbazole is the most resistant and 3-methylcarbazole is more resistant than other methylcarbazoles, thus both benzocarbazoles/total carbazoles and 3-methylcarbazole/total methylcarbazoles ratios rise with MN2 values. The bio-resistant sequence of dimethylcarbazole(DMC) is N–H[C1]semi-shielded > exposed > shielded isomers. Compared to the PM level, the Manco scale is more suitable to evaluate the variation patterns of pyrrolic compounds by expressing the level of biodegradation quantitatively with higher resolution than PM level.